Endogenous Housing Market Cycles - Trond Borgersen; Dag Einar Sommervoll; Tom Wennemo (Statistics Norway, Research Department, 2006)
Housing markets tend to display both positive serial correlation as well as a considerable volatility over time. We present a stochastic model illustrating the connection between adaptive expectations and market fluctuations. All macro economic and demographic variables stay fixed over time and price movements are driven by expectations only. In the case where agents face unconstrained mortgage financing, the housing market oscillations are regular and depend on mortgage to income ratios. When credit institutions are introduced, which view houses as mortgage collaterals, the dynamics get complex. Periods of mild oscillations are mixed with violent collapses in an unpredictable manner.
Keywords: 330; Heterogeneous agents; adaptive expectation; credit score models; house price cycles